2019
DOI: 10.1186/s12913-019-4834-2
|View full text |Cite
|
Sign up to set email alerts
|

Explaining the successes and failures of tuberculosis treatment programs; a tale of two regions in rural eastern Uganda

Abstract: BackgroundOptimally performing tuberculosis (TB) programs are characterized by treatment success rate (TSR) of at least 90%. In rural eastern Uganda, and elsewhere in sub Saharan Africa, TSR varies considerably across district TB programs and the reasons for the differences are unclear. This study explored factors associated with the low and high TSR across four districts in rural eastern Uganda.MethodsWe interviewed District TB and Leprosy Supervisors, Laboratory focal persons, and health facility TB focal pe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…A previous study in eastern Uganda reports that inadequate financing of the TB control program and deficiencies in the implementation of the CB-DOTS strategy is associated with suboptimal treatment success [ 18 ]. The study further showed that the disappearance of symptoms of TB especially after treatment initiation results in DTT [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study in eastern Uganda reports that inadequate financing of the TB control program and deficiencies in the implementation of the CB-DOTS strategy is associated with suboptimal treatment success [ 18 ]. The study further showed that the disappearance of symptoms of TB especially after treatment initiation results in DTT [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study in eastern Uganda reports that inadequate financing of the TB control program and deficiencies in the implementation of the CB-DOTS strategy is associated with suboptimal treatment success [ 18 ]. The study further showed that the disappearance of symptoms of TB especially after treatment initiation results in DTT [ 18 ]. Physical and economic barriers have been reported in a previous study as one of the reasons for not completing required sputum smear monitoring visits [ 19 ], emphasizing that people with TB face several barriers along the pathway to continuing with treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In Kumi district, rural eastern Uganda, almost three in 10 people travel ≥5 km (km) to access a health facility, public or private [9] . The majority of people with TB usually walk to receive TB services at these health facilities and face physical and economic barriers [10] . A patient is required to make a minimum of eight visits during the 6-month treatment period, with four visits in the first two months and a monthly visit in the last four months.…”
Section: Introductionmentioning
confidence: 99%
“…First, when discussing government spending including health expenditure, we must recognize the governance issues specific to poor countries, including such topics as democratization, corruption control, capacity-building, and electoral and judicial systems [2]. Although many studies in [2][3][4][5][6][7] argue for the importance of sustained public health programs and systems, the rise in government spending in many poor countries can slow or be repealed. Indeed, by using a panel dataset for 111 countries from 1984 to 2004, the share of GDP devoted to government expenditure in developed countries such as the United States has been steady and increasing since 1970, while government expenditure in developing countries over the past three decades has shown an inconsistent trend [8].…”
Section: Introductionmentioning
confidence: 99%